1996
DOI: 10.1093/oxfordjournals.alcalc.a008168
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Related Admissions to an Inner City Hospital Intensive Care Unit

Abstract: We investigated the impact of alcohol-related medical emergencies on health care utilization in an inner city hospital medical intensive care unit (ICU). Data from 200 consecutive admissions to the medical ICU were collected prospectively. The major reason for each patient's admission to the ICU was recorded and the causal relationship between alcohol abuse and the admission diagnosis was determined. Clinical and demographic data as well as the insurance status and cost of goods and services delivered were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 7 publications
1
26
1
1
Order By: Relevance
“…Alcohol consumption increases the risk of intensive care admission and of hospital death in men [9], and is directly related to the admission in 21 to 28% of ICU patients [10,11,12]. Drinking problems have been reported in 37.9% of ICU patients [4], and alcohol-related conditions described in 44 to 51% of gastroenterology inpatients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption increases the risk of intensive care admission and of hospital death in men [9], and is directly related to the admission in 21 to 28% of ICU patients [10,11,12]. Drinking problems have been reported in 37.9% of ICU patients [4], and alcohol-related conditions described in 44 to 51% of gastroenterology inpatients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the Intensive Care National Audit and Research Centre (ICNARC) database demonstrated that admissions to intensive care [6]. Previous studies assessing the effect of alcohol on admissions to ICUs have been single-centred studies or database reviews, or have studied a population that is not comparable to that of Scotland [7][8][9][10]. We therefore undertook the first prospective national study to ascertain the impact of alcohol-related admissions to ICUs.…”
mentioning
confidence: 99%
“…Alcoholism accounted for 21% of all admissions to a medical ICU in one study, with AWS being the most common alcoholism-related diagnosis (8). These patients are typically more difficult to manage than those in detoxification units or wards as they require massive doses of benzodiazepines or other drugs for treatment of alcohol withdrawal.…”
mentioning
confidence: 99%